2018
DOI: 10.21037/atm.2018.04.42
|View full text |Cite
|
Sign up to set email alerts
|

Current advances of targeting HGF/c-Met pathway in gastric cancer

Abstract: Despite the advances in systemic chemotherapy, gastric adenocarcinoma (GC) remains the third most common cause of cancer-related deaths with poor prognosis. The heterogeneity of GC indicates that novel biomarkers should be established in order to further classify tumors and develop individual targeted therapies. High-quality preclinical and clinical research has demonstrated that growth factor (HGF)-hepatocyte growth factor receptor (c-Met) pathway plays a pivotal role on the growth, survival and invasiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 82 publications
0
26
0
4
Order By: Relevance
“…[245][246][247][248] HGF is secreted mostly from mesenchymal tissues and is currently the only known ligand for MET. Its tissue and serum expression levels are related to poor prognosis of patients with different malignant tumors, such as breast, 249 esophageal, 250 and gastric cancers, 251 and especially CRC. Patients with advanced CRC have elevated serum HGF at diagnosis and decreased levels after cancer resection.…”
Section: The Hgf/c-met Pathwaymentioning
confidence: 99%
“…[245][246][247][248] HGF is secreted mostly from mesenchymal tissues and is currently the only known ligand for MET. Its tissue and serum expression levels are related to poor prognosis of patients with different malignant tumors, such as breast, 249 esophageal, 250 and gastric cancers, 251 and especially CRC. Patients with advanced CRC have elevated serum HGF at diagnosis and decreased levels after cancer resection.…”
Section: The Hgf/c-met Pathwaymentioning
confidence: 99%
“…It can occur by protein overexpression, gene amplification, increased HGF ligand autocrine expression, enhanced paracrine ligand-mediated stimulation, inadequate c-MET degradation, ligand-independent activation and rarely gene mutation, 19 in addition to the role of environmental conditions such as inflammation and hypoxia. 24 The most common mechanism of MET pathway abnormal activation in GC is via protein overexpression with resultant excessive kinase activation. MET protein expression on immunohistochemistry (IHC) is predominantly detected in 50-65% of GC.…”
Section: -Kinase (Pi3k)/akt Extracellular Signal-regulated Kinase (Ementioning
confidence: 99%
“…Therapeutically exploiting molecular biomarkers, including MET , in EGC has been plagued by multiple barriers, among the most important of which is tumoral heterogeneity. Despite, encouraging phase II studies of c‐MET antibodies (rilotumumab, onartuzumab), larger phase III EGC studies using the same screening criteria for c‐MET positivity revealed no survival benefits, regardless of c‐MET staining [46]. Larger efforts to assess for concordance between tissue (including both primary and metastatic sites) and blood (circulating tumor DNA) in order to evaluate the effect of tumor heterogeneity on response, as well as the impact of other molecular features, such as the presence of RTK co‐amplification, may aid in refining the population who are most likely to benefit from MET‐directed therapies, either alone or in combination.…”
Section: Resultsmentioning
confidence: 99%